2014
DOI: 10.1521/jscp.2014.33.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Parental Personality, Stress Generation, and Infant Temperament in Emergent Parent-Child Relationships: Evidence for a Moderated Mediation Model

Abstract: There is increasing research evidence supporting the assumption that transactional associations between parent and child characteristics need to be taken into account in order to more fully understand the dynamics within emergent parent-child relationships. This study focuses on transactional associations among parental self-criticism and dependency, parenting stress, child temperament, and emotional availability. Data from a two-wave, 1-year longitudinal study in a community sample of 79 first-time parents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Biringen, Skillern, Mone, & Pianta, ; Lehman, Steier, Guidash, & Wanna, ; Sagi, Koren‐Karie, Gini, Ziv, & Joels, ). In line with these findings, in another study (Casalin, Tang, Vliegen, & Luyten, ), we found that both parental self‐criticism and dependency assessed in infancy were associated with lower levels of dyadic emotional availability in toddlerhood and that these associations were fully mediated by parenting stress. However, the two‐wave design of the present study limits our ability to further clarify these mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…Biringen, Skillern, Mone, & Pianta, ; Lehman, Steier, Guidash, & Wanna, ; Sagi, Koren‐Karie, Gini, Ziv, & Joels, ). In line with these findings, in another study (Casalin, Tang, Vliegen, & Luyten, ), we found that both parental self‐criticism and dependency assessed in infancy were associated with lower levels of dyadic emotional availability in toddlerhood and that these associations were fully mediated by parenting stress. However, the two‐wave design of the present study limits our ability to further clarify these mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…Thirdly, due to the cross-sectional design of the study, conclusions about causality, and in particular about the direction of the mediational effect, have to be drawn carefully. Furthermore, other possible covariates that have shown relations to maternal EA, such as child temperament [53], social support [54], and maternal history of trauma [55], were not assessed in the present study. Another factor that might be interesting to investigate is the role of maternal intelligence, as it could be related to maternal ToM and might have a moderating role with regard to the prediction of maternal EA.…”
Section: Discussionmentioning
confidence: 99%
“…Effortful control has been shown to buffer the detrimental impact of low family income, maternal stress, and poor home environment on children's internalizing and externalizing problems (Lengua, Bush, Long, Kovacs, & Trancik, ), as well as protect against the emergence of conduct problems among youth with parents deployed in the military (Morris & Age, ). Among infants, one prior report found that orienting/regulation buffered the risk effect of parents’ self‐criticism on poor parent–child relationships (Casalin, Tang, Vliegen, & Luyten, ). Results from the present study provide further evidence that a regulatory dimension of temperament can buffer the impact of maternal stress on child stress responses as early as 12 months of age.…”
Section: Discussionmentioning
confidence: 99%